Small molecule STAT3/5 inhibitors exhibit therapeutic potential in acute myeloid leukemia and extra-nodal natural killer/T cell lymphoma - Pölöske, Daniel; Sorger, Helena; Schönbichler, Anna; de Araujo, Elvin D.; Neubauer, Heidi A.; Orlova, Anna; Timonen, Sanna H.; Abdallah, Diaaeldin I.; Ianevski, Aleksandr; Kuusanmäki, Heikki; Surbek, Marta; Wagner, Christina; et al. (bioRxiv, 2023)
The oncogenic transcription factors STAT3, STAT5A and STAT5B are essential to steer hematopoiesis and immunity, but their enhanced expression and activation drives the development or progression of blood cancers. Current therapeutic strategies focus on blocking upstream tyrosine kinases, but frequently occurring resistance often leads to disease relapse, emphasizing the need for more targeted therapies. Here we evaluate JPX-0700 and JPX-0750, which are STAT3/5-specific covalent cysteine binders that lead to growth arrest of acute myeloid leukemia (AML) and natural killer/T cell lymphoma (NKCL) cell lines in vitro and in vivo, as well as reduce cell viability of primary AML blasts ex vivo. Our non-PROTAC small molecular weight degraders selectively reduce STAT3/5 activation and total protein levels, as well as downstream target oncogene expression, exhibiting nanomolar to low micromolar efficacy. We found that both AML and NKCL cells hijack STAT3/5 signaling through either upstream activating mutations in tyrosine kinases, activating gain-of-function mutations in STAT3, mutational loss of negative STAT regulators, or genetic gains in anti-apoptotic, pro-proliferative or epigenetic-modifying STAT3/5 targets. Moreover, we have shown synergistic inhibitory action of JPX-0700 and JPX-0750 upon combinatorial use with approved chemotherapeutics (doxorubicin, daunorubicin, cytarabine), epigenetic enzyme blocker vorinostat, tyrosine kinase inhibitor cabozantinib or BCL-2 inhibitor venetoclax. Importantly, JPX-0700 or JPX-0750 treatment reduced leukemic cell growth in human AML/NKCL xenograft mouse models without adverse side effects. These potent small molecule degraders of STAT3/5 could propel further clinical development for use in AML and NKCL patients.